Treatment of Gustilo-Anderson type III open fractures with segmental long bone loss secondary to gunshot and war ınjurıes in paediatric patients with bone segment transport by the limb reconstructıon system (LRS). Issue 4 (April 2023) - Demir, Tugcan; Kilinccioglu, Namik Kemal; Dogramaci, Yunus
Abstract: Objective: The information on firearm- or explosive-related extremity injuries in children is very limited. Reports of segmental bone loss due to these types of fractures are even rarer and the treatment remains a problem. There has been no report of distraction osteogenesis with limb reconstruction system (LRS) specifically in children. We evaluated the treatment results of Gustilo–Anderson type 3 open fractures with segmental bone loss due to firearm injuries by distraction osteogenesis performed with LRS in skeletally immature patients. Methods: Nine patients with Gustilo–Anderson (GA) type 3 open fractures with segmental bone loss due to firearm injuries who had not completed their skeletal development were included. Two of the patients had GA type 3a, four had type 3b, and the remaining three had type 3c. Bony and functional assessment was conducted using Association for the Study and Application of the Methods of Illizarov (ASAMI) criteria. Results: Mean follow-up period was 20.1 months (range 5.5–35 months). The mean bone loss was 45.5 mm (range 15–80 mm) before the treatment started. The mean time of external fixation (day) was 180.6. The mean distraction index (distraction period per cm) was 11.3 day/cm. The mean time for bone union index (duration of bony union per cm) was 33.7 days/cm. Bony union was achieved in all patients at the end of the treatment. Bony results as per ASAMI score were excellent in seven fractures and good in three. Functional results were excellent in five patients, good in two, and fair in two. We had no fair or poor results with respect to bony results but had two fair functional results. Conclusions: LRS provides a good treatment choice for children with fractures with segmental bone loss due to firearm injuries. It also provides easy access to the wound with its monolateral construction. Graphical abstract: Image, graphical abstract